Piero di Cosimo : painter of faith and fable - Piero di Cosimo : painter of faith and fable (Conference) (2015 : Istituto universitario olandese di storia dell'arte); Geronimus, Dennis, 1972-; Kwakkelstein, Michael W., 1963- (Leiden ; Boston : Brill, 2019)
2015 could rightly be called 'The Year of Piero di Cosimo'. Piero's (1462-1522) critical fortunes have been much revived and his admirers? sense of curiosity piqued by two exhibitions, organized by the National Gallery of Art, Washington, DC, and the Galleria degli Uffizi, Florence. Together, the exhibitions marked and celebrated a pair of firsts. The first-ever major retrospectives devoted entirely to Piero?s artistic career and the first joint-exhibition collaboration between the National Gallery of Art and the Uffizi in the distinguished history of the two institutions. It could be said that the study of Piero di Cosimo belongs no less to the history of imagination than to the history of art. As was true for Giorgio Vasari five centuries ago, Piero?s highly personal visual language remains a moving target for modern scholars. Yet, as surprising and alluringly strange as his pictorial solutions appear, it may be claimed that we have never known or understood as much about Piero as we do today. Freed from the powerful spell of Vasari?s biography-cum-cautionary tale, the Piero that emerges is not solely a conjurer of the uncanny, but a sensitive observer of the natural and manmade worlds, humans and beasts, surfaces and coloristic effects, phenomena material and ephemeral.
Telling tales: The kaleidoscopic art of Piero di Cosimo (1462-1522) / Dennis Geronimus -- From Ancilla Domini to Madonna del Parto : observations on Piero di Cosimo's Marian imagery / Alessandra Galizzi Kroegel -- L'altare del Pugliese nella chiesa Spedale degli Innocenti : un esempio di dialogo fra pittura e scultura / Elena Capretti -- Real or imagined? Exotic animals in Piero di Cosimo's mythologies / Marina Belozerskaya -- The 'Fantasia' of the cricket in Piero di Cosimo's Vulcan and Aeolus / Sarah Blake McHam -- Rara Avis: Piero di Cosimo and the birds he painted / Roberta J.M. Olson -- Piero di Cosimo's Nymph and the hallmark of Artemis / Ianthi Assimakopoulou -- Beautiful monsters: The language of empathy and grief in Piero di Cosimo's representation of animals and human-animal hybrids / Dennis Geronimus -- The question of centaurs: Lucretius, Ovid, and Empedokles in Piero di Cosimo / Guy Hedreen -- Piero di Cosimo and Netherlandish painting / Paula Nuttall -- Piero and Ghirlandaio: Drawing the figure / Jean K. Cadogan -- Deconstructing the underdrawing in Piero di Cosimo's Construction of a palace / Elizabeth Walmsley -- La ricomposizione di un Piero di Cosimo perduto : il restauro della pala con Lo sposalizio mistico di S. Caterina e della lunetta con i due angeli che sorreggono la corona / Anna Teresa Monti e Lisa Venerosi Pesciolini -- Piero di Cosimo: Two angels return to Florence from Edinburgh / Lesley Stevenson.
"The thirteen essays comprising the present volume spring from the proceedings of a two-day conference hosted by The Dutch University Institute for Art History, scheduled to coincide with the final days of the Uffizi Piero exhibition in late September 2015."
English and Italian.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Piero, -- di Cosimo, -- 1462-1521 -- Congresses; Piero, -- di Cosimo, -- 1462-1521 -- Congrès.; Piero, -- di Cosimo, -- 1462-1521; ART -- History -- General; Conference papers and proceedings